Photo-responsive lignin fragment-based polymers as switchable adhesives. Issue 8 (31st January 2023) - Sinha Roy, Pallabi; Mention, Matthieu M.; Patti, Antonio F.; Garnier, Gil; Allais, Florent; Saito, Kei
Abstract : A photo-reversible and reusable polymer adhesive was designed and synthesized from bio-resources. Six unique monomers were evaluated via structure–property analysis, and the best polymer adhesive performance was optimized using statistical methods. Abstract : Easily detachable and reusable adhesives are attractive as single-use adhesive replacements to reduce waste and promote reuse, recycling, or even upcycling options. Lignin, the second most abundant polymer and a byproduct of the paper-pulp industry, was utilized to design a novel, highly tunable reversible polymer adhesive. The approach adopted was to take advantage of the photo-responsive property of the α, β-unsaturated ester moiety of the p -hydroxycinnamic acid structure synthesized in this work using lignin-oxidation compounds and modified to attain reversible adhesion switching. The reversibility is achieved by the exposure of UV light that cleaves the covalent cyclobutane rings originally formed from the α, β-unsaturated bond of the ester, which softens the material and makes it easily separable. The original polymer structure can be established again by recrosslinking to offer reworkability. The design of experiments (DoE) method was introduced to optimize the significant variables to achieve optimum lap shear strength for the adhesive. The effect of various structural aspects shows a high tunability of the structure to meet the property requirements. The design strategy of the polymer adhesive from renewable resources, along with the structure–property analysis mechanisms described in this work, can be implemented to engineer new bio-based and reusable adhesives.